Frontispiece: Unlocking the Drug Potential of the Bryostatin Family: Recent Advances in Product Synthesis and Biomedical Applications. Issue 6 (30th January 2020) - Wu, Rongzhen; Chen, Hongyu; Chang, Ninghui; Xu, Yuzhi; Jiao, Jiao; Zhang, Hailong
Abstract : Bryostatins, a class of naturally occurring macrocyclic lactones with eleven chiral centers, which were isolated from marine invertebrates, turned out as promising candidates for medicinal applications, including AIDS, Alzheimer's disease, and cancer. The ongoing work towards the total synthesis of bryostatins and structural analogues (bryologs) as well as the biomedical application of these compounds is summarized in the Review by J. Jiao, H. Zhang et al. on page 1166 ff.